Compressibility characteristics of compacted clay treated with cement, peat ash and silica sand - Mousavi S.; Wong L.S. (Penerbit Universiti Kebangsaan Malaysia, 2023)
ash; cement; compressibility; consolidation; embankment; one-dimensional modeling; peat; road; sand; silica; soft clay; soil mechanics